Association between plasma levels of BDNF and the antisuicidal effects of repeated ketamine infusions in depression with suicidal ideation. (November 2020) - Zheng, Wei; Zhou, Yan-Ling; Wang, Cheng-Yu; Lan, Xiao-Feng; Zhang, Bin; Zhou, Su-Miao; Yan, Su; Yang, Ming-Zhe; Nie, Sha; Ning, Yu-Ping
Background: This study is the first to examine the association between plasma levels of brain-derived neurotrophic factor (BDNF) and the antisuicidal effects of repeated ketamine infusions in depressed patients with suicidal ideation. Methods: Fifty-seven depressed patients with suicidal ideation received six ketamine infusions (0.5 mg/kg) during a 12 days period. Suicidality was measured with the Scale for Suicidal Ideations (SSI-part 1), item 10 of the Montgomery–Åsberg Depression Rating Scale (MADRS), and item 3 of the Hamilton Depression Rating Scale (HAMD) at baseline, 1 day after the first infusion (1 day), 1 day after the sixth infusion (13 days), and at 2 weeks after the last infusion (26 days). Plasma levels of BDNF were measured by enzyme-linked immunosorbent assay at baseline, 13 days, and 26 days. Results: Overall, 46 (80.7%) depressed patients with suicidal ideation had an antisuicidal response at 13 days. Despite a significant reduction in suicidal symptoms over time, no changes in plasma levels of BDNF were found after ketamine treatment when compared with baseline. Correlation analysis showed that no significant association was observed between the plasma levels of BDNF and the changes in the severity of suicidal symptoms as measured by SSI-part 1, item 10 of the MADRS, or item 3 of the HAMD at 1 day, 13 days, and 26 days (all p  < 0.05). Conclusion: Our results indicated that plasma levels of BDNF may not serve as a biomarker for determining the antisuicidal effects of six ketamine infusions in depressed patients with suicidal ideation.